Kemampuan Kompetensi Pedagogik Guru Sekolah Dasar dalam Proses Pembelajaran - Emy Crisnawati; Agus Kichi Hermansyah; Ratna Purwanty (Universitas Kanjuruhan Malang, 2022)
This study aims to analyze how the pedagogical competence of teachers in the learning process at SD Yapis 1 Merauke. The type of research used is qualitative research with 4 teachers as the subject. Data collection using interview, observation and documentation techniques. The analysis is to find out how the teacher's pedagogic competence in the learning process uses source triangulation, technique triangulation and member checks. The results showed that at SD Yapis 1 Merauke there were several pedagogical competence that have been implemented, namely the syllabus, learning teaching materials and learning approaches